THE EFFECTIVENESS OF USING THE DUOLINGGO APPLICATION IN IMPROVING STUDENTS’ MOTIVATION AND ENGLISH-SPEAKING SKILL AT UNIVERSITAS POTENSI UTAMA MEDAN - Amaniarsih, Dwi Suci; Asrul, Nurmahyuni; Juliana, Juliana; Ginting, Erwin (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This study aims to improve students' motivation and English-speaking skills by using the Duolingo application. The type of research applied in this study is a quasi-experimental method research type with a one group pre-test-post-test design approach, namely experimental research carried out on only one group, namely the experimental group without a comparison group or control group. The study was conducted on students of the English Study Program, Universitas Potensi Utama Medan, Semester I TA. 2024/2025, totaling 30 people. Based on the research results, it shows that the application Duolingo as a learning medium has been proven to be effective in improving students' English-speaking skills and increasing students' interest and motivation in participating in learning. It can be seen from the results of the percentage that has increased after the Duolingo application was implemented as a learning medium. In the pretest activity, the percentage of student completion scores only reached 30%, and student responses during the learning process were categorized as lacking, meaning that students seemed less motivated to participate in learning activities. While in the posttest activity there was a significant increase where there were 74% of students who experienced completion in learning to speak English and student responses during the learning process were categorized as good. This means that student interest and motivation in participating in learning have increased